Sistem Pakar Pengidentifikasian Jenis Kulis Wajah Dalam Pemilihan Msglow Series Menggunakan Naïve Bayes - Hasnidar, Hasnidar; Prasetyaningrum, Putri Taqwa (CV. Information Technology Training Center - Indonesia (ITTC), 2022)
There are still many problems with choosing treatment products that do not match the needs of their skin and skin type. Some people follow what their friends do or what is popular now, and numerous people still try to figure out their skin problems and types without first talking to an expert. Using MS GLOW Makassar as a case study, this research was done based on a needs history. The Naive Bayes method was used to make this system. The goal of designing a skincare selection expert system was to apply and use an expert system so that experts and non-experts could use it to choose skincare based on skin type. Based on 30 costumer data that the system and experts have tested by applying Naive Bayes, the accuracy rate was 100%